1995
DOI: 10.1017/s002202990003377x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and technological aspects of milks fermented by bifidobacteria

Abstract: Introduction and historical background Nomenclature and classification Taxonomic information Morphology Cell wall structure Carbohydrate utilization Ureasc activity Deoxyribonucleic acid (DNA) homology New Old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
23

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 120 publications
4
78
0
23
Order By: Relevance
“…fed infant faeces in the present study corroborates with Roberts et al (1985), Tamime et al (1995), Silvi et al (1996) and Martin et al (2009) who reported that human milk is favourable for the growth and sustenance of Bifidobacteria in the large intestine of infants. Wasilewska and Bielecka (2003) also isolated and identified fourteen bifidobacterial strains from faeces harbouring the gut of 3-month old breast fed infant.…”
Section: Isolate Identity Code Nosupporting
confidence: 92%
See 1 more Smart Citation
“…fed infant faeces in the present study corroborates with Roberts et al (1985), Tamime et al (1995), Silvi et al (1996) and Martin et al (2009) who reported that human milk is favourable for the growth and sustenance of Bifidobacteria in the large intestine of infants. Wasilewska and Bielecka (2003) also isolated and identified fourteen bifidobacterial strains from faeces harbouring the gut of 3-month old breast fed infant.…”
Section: Isolate Identity Code Nosupporting
confidence: 92%
“…The findings in Table 2 are in accordance with Tamime et al (1995) and Vlkova et al (2005) who reported the dominating species of Bifidobacteria in intestinal flora of breast fed infants as B. longum, B. breve and B. bifidum. Loquasto et al (2013) sequenced the genome of B. animalis subsp.…”
supporting
confidence: 89%
“…Most lactobacilli already have a beneficial effect in the small intestine, whereas the largest numbers of bifidobacteria are often found in the colon. Both probiotics are also reported to synthesize folic acid, niacin, thiamine, riboflavin, pyridoxine and vitamin K, which are slowly absorbed by the body (Tamine et al, 1995). L. acidophilus exhibits antagonistic activity against pathogenic bacteria, which are foodborne disease agents (Sanders and Klaenhammer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the majority of commercially available probiotic fermented milks in different markets of the world (ca 80 -100) are made with a mixture of non-traditional and traditional starter cultures, and detailed examples have been reported by Hoier (1992), Tamime et al (1995), Tamime & Marshall (1997), Holzapfel et al (1997) (1995), Maisnier-Patin et al (1996), Dave and Shah (1997), Marshall and Tamime (1997a), McAuliffe et al (1998), Papathanasopoulos et al (1998), Anderssen et al (1998), Kawai et al (1998), Suma et al (1998), van Reenen et al (1998, Yildirim andJohnson (1998), Farias et al (1999), Remiger et al (1999), Fujiwara et al (1999), Zhu et al (2000), Gänzle et al (2000).…”
Section: Commercial Probiotic Fermented Milk Productsmentioning
confidence: 99%